Research Trends in the Use of Augmented Reality in Engineering Education: A Bibliometric Analysis - Utami, Nisaudzakiah; Setiawan, Agus; Hamidah, Ida (IJIE (Indonesian Journal of Informatics Education), 2022)
This study aims to report on the overall research trend of research progress in the Augmented Reality (AR) field in engineering education. The research method used is bibliometric analysis (BA) using VoSviewer. The data is taken from the Scopus database. The findings show an increasing trend in citations and publications showing interest in using AR over the last decade. AR research in engineering education started in 2006 until now. Screening of selected articles from 2012 to 2022. The screening process based on inclusion and exclusion included the chosen language in English and based on the publication of final articles, resulting in a total of 858 articles. The results reveal that augmented reality, engineering education, and mobile learning are the most used keywords in the article. In contrast, the focus of the new article tends to be on augmented reality. In addition, the results show that the latest articles mostly focus on virtual and mobile learning. The most frequently used words in the abstract are engineering education, student, e-learning, education, and teaching. Recent articles have largely focused on students' and teachers' knowledge of technology-based learning. Billinghurst, Dede, and Martin are the most cited authors in this field, as they are the principal authors of AR. The journals cited are Computers & Education, Coeur Workshop Proceedings, Computers in Human Behavior, and the Journal of Science Education and Technology. The journal is the most prominent on the use of technology in education.